2020
DOI: 10.2174/1381612826666200813132951
|View full text |Cite
|
Sign up to set email alerts
|

Role of Histamine as a Peripheral Sympathetic Neuromediator and its Interrelation with Substance P

Abstract: : With this article we wanted to carry out an educational review about of the fundamental aspects related to the proposal of the existence of a peripheral sympathetic reflex regulated by Histamine, through its effect on presynaptic H3 type receptors, under the interaction of a sensory neurone that would be mediated by Substance P. In this respect, we consider it useful to highlight the role of Histamine, so we discuss some aspects about its history, metabolism, and function, as well as its interaction with H3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…At the hypogastric ganglion level, Atencio et al (2020) hypothesized that SP mediates the vicious circle between histamine and the noradrenergic sympathetic response via noradrenaline release [ 7 ]. Among the four histamine receptor subtypes, numerous reports demonstrated the presence of presynaptic histamine H 3 receptors in the autonomic nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the hypogastric ganglion level, Atencio et al (2020) hypothesized that SP mediates the vicious circle between histamine and the noradrenergic sympathetic response via noradrenaline release [ 7 ]. Among the four histamine receptor subtypes, numerous reports demonstrated the presence of presynaptic histamine H 3 receptors in the autonomic nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, histamine H 3 receptors act as autoreceptors and negatively affect histamine release itself [ 12 , 13 , 14 ]. Therefore, the presynaptic histamine H 3 receptor could be crucial in regulating the peripheral sympathetic reflex [ 7 ]. Consistently, Silver et al (2001) demonstrated that activation of histamine H 3 receptors in the peripheral sympathetic terminal inhibits the Na + /H + exchanger (NHE) activity, thus reducing the noradrenaline release during myocardial ischemia [ 15 ].…”
Section: Introductionmentioning
confidence: 99%